Ritual Body Dramaturgy in Turuk Laggai in the Pabetei Ritual of the Mentawai Community - Dian Permata Sari,; Zulfardi Darussalam; Afifuddin; Rasyidin; Haria Nanda Pratama (PT FORMOSA CENDEKIA GLOBAL, 2026)
Turuk Laggai is a ritual practice of the Mentawai people that is closely related to the Arat Sabulungan belief system, the ritual body, and the ecological relationship of the community with nature. The development of cultural tourism and social change has caused Turuk Laggai to shift in function from a sacred practice to a cultural performance, thus raising questions about the position of Turuk Laggai as a spiritual ritual or performative spectacle. This study aims to analyze the dramaturgy of the ritual body in Turuk Laggai in the Pabetei ritual of the Mentawai people through a performance studies approach. The focus of the research is directed at the Sikerei body, animal movement mimesis, Gajeuma music, and the performative atmosphere of the ritual. The study uses a qualitative method with a descriptive-interpretive approach. Data were obtained through literature studies, audiovisual documentation, and a review of previous research on Turuk Laggai and Mentawai community rituals. The analysis was conducted using a performance studies perspective to examine the relationship between the body, sound, ritual space, and spiritual experience in ritual performances. The results show that the Sikerei body works as a symbolic medium that connects humans with ancestral spirits and nature through body rhythm, movement repetition, trance, and animal mimesis. Ritual movements serve not only aesthetic functions but also represent the ecological and cosmological experiences of the Mentawai people. Gajeuma music plays a role in building a performative ritual atmosphere through repetitive rhythmic patterns that strengthen the emotional and spiritual experiences of the community. This research shows that Turuk Laggai is a form of total performance that presents an integration of body, music, space, and spirituality in a unified ritual aesthetic of the Mentawai people. This research is expected to contribute to the development of studies of ritual performing arts, particularly those related to the body, performativity, and cultural knowledge of indigenous communities in Indonesia.